(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: Several studies have demonstrated that acupuncture increases skin temperature. In particular, acupuncture techniques play an important role in enhancing blood flow to the skin and muscles. Additionally, Luo and Yuan acupoints are highly effective in clinical practice, although evidence remains limited. Therefore, this study was conducted to investigate the skin temperature at the Yuan acupoints on the Yin meridians when performing dispersal at the Luo acupoints on the Yang meridians. Methods: Sixty healthy participants were randomly assigned to two groups: Group A (no needle manipulation) and Group B (dispersal). Both groups received acupuncture at bilateral Luo acupoints on the Yang meridians. In Group B, needles were twirled for 1 minute at T1, T2, and T3. Skin temperature was measured using an infrared camera at both the Luo acupoints on the Yang meridians and the Yuan acupoints on the Yin meridians at five time points: T0, T1, T2, T3, and T4. Results: In the dispersal group, skin temperature at both the Luo and Yuan acupoints significantly increased at all post-acupuncture times (p<0.0125), except at bilateral Taichong acupoint (p>0.0125). When comparing the two groups, ∆T3 and ∆T4 at all points were significantly higher in the dispersal group than in the control group (p<0.0125), except at the Taichong acupoint (p>0.0125). Conclusion: Dispersal at the Luo acupoints on the Yang meridians increases skin temperature at Yuan acupoints on the Yin meridians with an exterior-interior relationship, except at the Taichong.